Physician Mental Workload Scale in China: Development and Psychometric Evaluation - Chao Li; Chuntao Lu; Yinhuan Hu; Qiang Fu; Samuel Governor; Liuming Wang; Lu Deng; Jinzhu Xie (BMJ Open)
Objective The purpose of our study is to develop a mental workload scale for physicians in China and assess the scale’s reliability and validity.Design The instrument was developed over three phases involving 396 physicians from different tiers of comprehensive public hospitals in China. In the first phase, an initial item pool was developed through a systematic literature review. The second phase consisted of two rounds of Delphi expert consultations and a pilot survey. The third phase tested the reliability and validity of the instrument.Setting Public hospitals in China.Participants A total of 396 physicians from different tiers of comprehensive public hospitals in China participated in this study in 2018.Primary and secondary outcome measures Cronbach’s α, content validity index, item-total score correlation coefficient, dimension-total score correlation coefficient and indices of confirmatory factor analysis.Results Six dimensions (mental demands, physical demands, temporal demands, perceived risk, frustration level and performance) and 12 items were identified in the instrument. For reliability, Cronbach’s α for the whole scale was 0.81. For validity, the corrected item-content validity index of each item ranged from 0.85 to 1, item-total score correlation coefficients ranged from 0.31 to 0.75, and the correlation coefficients between the dimensions and total score ranged from 0.37 to 0.72. The results of the confirmatory factor analysis showed that the goodness-of-fit indices of the scale were satisfactory.Conclusion The instrument showed good reliability and validity, and it is useful for diagnosing the mental workload of physicians.